A comparative study of IP Versions 4, 5, and 6 - Naseef Husam Mohammad alnile; Yasmin Makki Mohialden; Majd S. Ahmed (Newinera Publisher, 2021)
This research examines the Internet Protocol (IP) versions 4, 5, and 6, as well as the differences between them and which protocol is more suitable for the future of the internet, among other things. Through this research, we have established the most advantageous characteristics of these protocols, as well as the specific elements that each protocol uses to allow the internet network to operate at maximum capacity. The main aim of this study is to discover which of the internet protocols, IPv4, IPv5, or IPv6, is the most widely used. IPv4 is the most widely used protocol, followed by IPv5. The most essential elements of getting a more relevant job on the internet network are highlighted in this article. It all comes down to how IP protocols operate and what they accomplish.